2021
DOI: 10.3390/su13148007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Characteristics and Activities of the Board of Directors on Sustainable Development Goal (SDG) Disclosures: Empirical Evidence from Southeast Asia

Abstract: This study aimed to analyze the board of directors’ commitment to the Sustainable Development Goals (SDGs) by looking at the influence of the characteristics and activities of the board of directors and the existence of Corporate Social Responsibility (CSR) committees on disclosures regarding the SDGs. The directors’ characteristics that were analyzed in this research included the board size, the proportion of independent directors, the presence of female directors, and the presence of foreign directors. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 47 publications
5
24
0
9
Order By: Relevance
“…Many studies suggest that the size of the board matters when it comes to corporate responsibility, arguing that larger boards offer more diverse perspectives that should strengthen their monitoring roles and lead to better CSR performance [21,23,33,34]. Results, however, have been mixed; while some studies have found no relationship between board size and CSP [21] or disclosures [35], others have found a positive association [10,33]. Paradoxically, it appears that larger boards are also more positively associated with negative CEP outcomes, such as environmental litigation [36] and environmental concerns [14].…”
Section: Corporate Governance and Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies suggest that the size of the board matters when it comes to corporate responsibility, arguing that larger boards offer more diverse perspectives that should strengthen their monitoring roles and lead to better CSR performance [21,23,33,34]. Results, however, have been mixed; while some studies have found no relationship between board size and CSP [21] or disclosures [35], others have found a positive association [10,33]. Paradoxically, it appears that larger boards are also more positively associated with negative CEP outcomes, such as environmental litigation [36] and environmental concerns [14].…”
Section: Corporate Governance and Sustainabilitymentioning
confidence: 99%
“…Foreign boards have also been shown to engage in more CSR activities [41]. Lastly, the presence of different board committees, such as a CSR or an environmental or sustainability committee, have also been associated with a greater stakeholder orientation towards corporate governance [42], a greater commitment to SDG disclosures [35], and better social or environmental performance [37,43]; however, this support, too, has not been universal [44].…”
Section: Corporate Governance and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, expertise is an alternative proxy to measure boards' ability to provide their services (Cunningham, 2008;Wagner, 2011). Expertise is inherently multi-dimensional and ranges from knowledge of the industry (Dass et al, 2014) to firm specific information and other director-craft competences such as political connections, financial literacy or sustainable development goals (Ali et al, 2022;Ammari, 2022;Gilani et al, 2021;Naheed et al, 2021;Crifo et al, 2018;Sekarlangit & Wardhani, 2021;Burak Guner et al, 2008;Mire, 2016). Directors develop their expertise through their education, their professional experience and their business activity with the firm (Anderson et al, 2011;Reeb & Zhao, 2013).…”
Section: Literature Review and Conceptual Framework Developmentmentioning
confidence: 99%
“…Expertise refers to the set of knowledge and competencies related to directors' duties, that is financial and extra-financial (sustainable development) information (see e.g. Dass et al, 2014;Sekarlangit & Wardhani, 2021). Independence captures the "distance" or connection between board members and the CEO, a higher independence meaning a lower propensity of collusion between the board and the CEO (see e.g.…”
Section: Timing Of the Modelmentioning
confidence: 99%